The audiovisual resources and the development of both listening and speaking skills in students of 9th grade at Bernardita Correa Delgado Public School during the school year 2018-2019 - Jiménez Santillán, Carlos Alberto (2020)
Since last decades, the English language is considered a powerful tool used by people to communicate with others. As an international language, English is spoken in many countries around the world. Therefore, English language learning is an inescapable necessity for human beings. However, in the educational field, it presents serious difficulties for many students when learning language skills. Some of these skills that they find more difficult to develop are speaking and listening. It is evident that many students have difficulty to speak fluently, pronounce properly and make an accurate use of their oral production. While in listening, they have difficulty to comprehend basic listening texts. The principal factor to this problematic situation lies on the traditional methodology that the teacher uses. As a consequence, the students do not show much interest, in some cases, they consider English as a boring subject. The audiovisual resources in the educational system are one of the fundamental factors that defines the need to modify the traditional teaching schemes. Nowadays, the students feel more interest when they learn with images or sounds. EFL teachers must know that these audiovisual resources may facilitate better learning, getting students more motivated and interested. Therefore, the main purpose of this research project is to determine the influence of the audiovisual resources on the development of the English Speaking and Listening skills in ninth grade students………….